Homicide drop in seven European countries: General or specific across countries and crime types? - Suonpää, Karoliina; Kivivuori, Janne; Aarten, Pauline; Ahven, Andri; Granath, Sven; Markwalder, Nora; Skott, Sara; Thomsen, Asser H.; Walser, Simone; Liem, Marieke (European journal of criminology, 2024)
This study examines homicide trends in seven European countries – Denmark, Estonia, Finland, the Netherlands, Scotland, Sweden and Switzerland – all of which manifested a substantial drop in homicide mortality between 1990 and 2016. By using data from the European Homicide Monitor, a coding scheme created to enable cross-country comparisons, combined with the national cause-of-death statistics, we explore generality versus specificity of the homicide drop. We examine changes in the demographic structure of victims and offenders and disaggregate homicides by different subtypes of lethal incidents, such as family-related homicides referring to conflicts between family members, and criminal milieu homicides occurring in the context of robberies, gang-related conflicts or organised crime. Results point to the generality of the drop: in most of the countries studied, the declining trend included all homicide types. The overall decline in homicide mortality was driven mostly by the decline in male victimisation and offending. In most of the countries, the gender distribution of victims and offenders changed only slightly during the study period, whereas the development of the distribution of homicide types manifested greater diversity. Our findings illustrate the benefits of disaggregated analyses in comparative homicide research.